2018
DOI: 10.1021/acssuschemeng.8b04694
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Lithium Ions from Salt Lake Brine with a High Magnesium/Lithium Ratio Using Heteropolyacid Ionic Liquid

Abstract: A fluoride-free ionic liquid 1-butyl-3-methylimidazolium phosphotungstate ([Bmim] 3 PW 12 O 40 ) was synthesized and first used as co-extraction reagent for recovery of lithium ions from salt lake brine with a high Mg/Li ratio. Fourier transform infrared spectra (FT-IR), nuclear magnetic resonance (NMR) and thermogravimetric analysis (TGA) were used for characterizations of the prepared ionic liquid. Tributyl phosphate (TBP), [Bmim] 3 PW 12 O 40 , and dimethyl phthalate (DMP) were used as extractant, co-extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…In such extraction, the cations of the ionic liquids enter into the aqueous solution and the anions are involved in the complex formation with Li + . [19][20] Following this discovery, many kinds of ionic liquids [21][22] and salts (e.g. NaClO4 and NaB(Phen)4) with symmetric anions were found to be similar in extraction capability of lithium with TBP.…”
Section: Besides [Fecl4] - [Pf6]mentioning
confidence: 99%
“…In such extraction, the cations of the ionic liquids enter into the aqueous solution and the anions are involved in the complex formation with Li + . [19][20] Following this discovery, many kinds of ionic liquids [21][22] and salts (e.g. NaClO4 and NaB(Phen)4) with symmetric anions were found to be similar in extraction capability of lithium with TBP.…”
Section: Besides [Fecl4] - [Pf6]mentioning
confidence: 99%
“…To this end, molecular design of task‐specific monomers for surface modification is crucial. Recently, ionic liquids show high efficiency in liquid extraction, ion sieving, and gas separation, [ 31–34 ] yet ionic liquid membranes have not been reported for high performance lithium separation from salt lake brines. In particular, previous ionic liquid monomers contain only one reactive group that limits the in‐depth modification and structure modulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the synergic solvent extraction of Li by the TBP/FeCl 3 system, the role of FeCl 3 is to form an anionic [FeCl 4 ] − complex that can further form an ion pair with the cation [Li(TBP) x ] + ( x = 1, 2), as shown in Equation (). In recent years it was found that anions of ionic liquids (ILs), such as [PF 6 ] − , [NTf 2 ] − , [B(Phen) 4 ] − and [PW 12 O 40 ] 3− can replace [FeCl 4 ] − as counter anions, provided that the cations of the ILs are hydrophilic 21‐25 . Therefore TBP can also synergically extract Li from Mg‐containing solutions in combination with ILs, although the use of ILs instead of FeCl 3 is not economic because of the high cost of ILs and the difficulty of recycling the ILs. Fe3++Li++4Cl+xtrueTBP¯true0.25emLiTBPx·FeCl4¯ where x = 1, 2, and the overbar means that the compound resides in the organic phase.…”
Section: Introductionmentioning
confidence: 99%